De la santé environnementale à la justice environnementale : l'enjeu de l'asthme infantile dans le South Bronx (New York) - Flaminia Paddeu (Développement Durable et Territoires)
Childhood asthma is a respiratory disease whose prevalence is increasing in industrialized countries. In New York, childhood asthma is twice the national average, and even three times in the South Bronx, a low-income industrialized area located North of the city. The increase of asthma tends to be more and more linked to environmental factors such as air pollution. Originally a public health problem, asthma has become an environmental health challenge. But since the 1980's, asthma in New York has been used as a political and rhetorical tool serving environmental justice advocacy. The case study of Hunts Point (South Bronx) allows us to study strategies for the use of asthma by local activists, as an issue at the intersection between air pollution and social and racial inequalities.